Some Types of Convergence for Negatively Dependent Random Variables under Sublinear Expectations - Ruixue Wang; Qunying Wu (Discrete Dynamics in Nature and Society)
In this paper, we research complete convergence and almost sure convergence under the sublinear expectations. As applications, we extend some complete and almost sure convergence theorems for weighted sums of negatively dependent random variables from the traditional probability space to the sublinear expectation space.